Constructing Religious Harmony through Rhetoric: An Analysis of Vivekananda's Selected Speeches - Ghimire, Surendra Prasad (Journal of Business and Social Sciences, 2021)
This research article reports how rhetorical elements used in the speeches of Swami Vivekananda at World Parliament of Religions supports to construct the religious harmony in the world. This study is based on qualitative interpretative research design and employs the theoretical ideas based on Richard Andrews to interpret the various rhetorical devices in his selected speeches. Furthermore, this paper analyzes the use of arguments in his speeches by using the idea developed by Stephen Toulmin and his visual rhetoric is analyzed using the idea based on Tracey Owens Patton. Findings show that use of rhetorical elements in his speeches contributes to make his arguments stronger to construct the religious harmony among the world religions despite the apparent contradiction among them. He incorporated rhetorical devices in his speeches such as metaphors, similes, parallelism, appropriate dictions and repetitions to persuade the audience to establish his claim more effectively by making simple and understandable. His rhetoric of spiritualization of religions with the support of interpretation of Vedic philosophy contributes to integrate the world religions by stating that every human being has been created equally having the body and immortal spirit with them. His visual rhetoric including attractive bodily appearance, confidence and commanding voice helped him to attract the attention of the large mass of audience towards him. Findings of this article contribute to a better understanding that appropriate use of rhetorical elements supports to make effective communication and helps to persuade the audience to achieve the goal.